Framework for Evaluation of the IT&C Audit Metrics Impact - Marius POPA (Informatică economică, 2011)
The paper defines an assessment system for performance of IT&C audit process. The analytical models of performance indicators are provided together with the interpretation of their results. Performance levels catch the quality characteristics of the audit processes carried out for distributed informatics systems. Also, the paper presents a performance assessment framework for audit processes and a performance audit methodology. The impact of performance indicators is defined as the organization’s income after performance audit recommendation implementing. Methods and techniques for performance assessment are provided for audit processes of the distributed informatics system. The impact levels of performance indicators are calculated before implementation of the performance recommendation and after that to establish whether the performance audit increases the quality of IT&C audit processes.